The importance of Professional Happiness on Patient Satisfaction. The case of physiotherapy professionals. - Jacobshon, Lia (2019)
In recent years research on organizational happiness has been increasing but instruments to measure happiness at work, considering organizational factors, are scarce. This study aims to validate a scale to measure organizational happiness among physiotherapists and its relationship with patient satisfaction. For that we will implement an Organizational Happiness Scale to physiotherapists and the Physical Therapy Patient Satisfaction Questionnaire to their patients. At the end two major outcomes will be achievable: (i) the study of validation and reliability of a happiness organizational scale to be used among physiotherapist and, (ii) to understand if happiest physiotherapists have more satisfied patients. Previous research demonstrates the positive impact of satisfaction on patient rehabilitation. This study will provide knew knowledge on the contribution of a happy physiotherapist professional for that.